Etiamsi omnes, ego non: an exploratory study of argument types in separate opinions - Brambilla, Emanuele (Comparative Legilinguistics, 2025)
The present paper explores the nature of argument types in separate opinions by analysing a corpus of ten judgments issued in English by the European Court of Human Rights (ECtHR) between 2020 and 2024. The qualitative analysis primarily draws on the pragma-dialectical categorisation of argument schemes to investigate whether the separate opinions at issue reveal a predilection by ECtHR judges for symptomatic, comparison or causal arguments. The results suggest that the three argument types are invariably used, in that they enable ECtHR judges to shape the complex argumentative defence of their standpoints. Symptomatic arguments mostly occur as arguments from authority; comparison arguments are mainly harnessed to establish analogies with previous judgments; and pragmatic arguments are used primarily to warn against the detrimental legal consequences of the majority decisions. Although the latter occur less frequently, the three argument types all appear functional to enhancing the acceptability of contra-argumentation in separate opinions.